Enhancing SEO in Single-Page Web Applications in Contrast With Multi-Page Applications - Karolina Kowalczyk; Tomasz Szandala (IEEE Access, 2024)
This paper comprehensively reviews methods for improving single-page applications’ visibility (SPAs) and user experience, focusing on the intricacies of search engine optimisation (SEO). This research contrasts the complexities and challenges in optimising SEO in SPAs instead of conventional multi-page applications (MPAs). It identifies vital optimisation methods and evaluates their applicability in the contemporary web landscape. The research method involves implementing the explored optimisation techniques across three distinct projects utilising emerging technologies for SPA, MPA, and a hybrid approach using Isomorphic JavaScript. These applications are systematically examined and subjected to a comparative analysis to assess the effectiveness of the optimisation strategies before and after applying the optimisation strategies. The empirical results substantiate that adopting an innovative approach to Client-Side rendering for the initial page load, combined with traditional SEO practices, performance enhancements, and tailored methodologies for specific technologies, facilitates SEO optimisation in SPAs at a level commensurate with MPAs. The findings of this work hold significant implications for web developers, offering insights and actionable strategies to augment visibility and performance in search engine results. By bridging the theoretical understanding with hands-on application and empirical analysis, the research contributes to the evolving field of web application development. It underscores the critical role of SEO optimisation in the context of SPAs, highlighting its importance for search engine rankings and overall user engagement and satisfaction. Code is available on GitHub:https://github.com/karolinakowalczyk?tab=repositories&q=TravelBLog